Perception of smile esthetics by laypeople of different ages - Chompunuch Sriphadungporn; Niramol Chamnannidiadha (SpringerOpen, 2017)
Abstract Background Age is a factor affecting smile esthetics. Three variables of smile esthetics associated with the maxillary anterior teeth and age-related changes have recently received considerable attention: (i) the incisal edge position of the maxillary central incisors, (ii) the maxillary gingival display, and (iii) the presence of a black triangle between the maxillary central incisors. The aim of this study was to evaluate the influence of age on smile esthetic perception based on these three variables in a group of Thai laypeople. Methods The smiles were constructed from a photograph of a female smile. Smile photographs were altered in various increments using three variables: the incisal edge position of the maxillary incisors, gingival display, and a black triangle between the maxillary central incisors. The photographs were shown to a group of 240 Thai laypeople. The subjects were divided into two groups: a younger group, 15-29 years old (n = 120) and an older group, 36-52 years old (n = 120). Each subject was asked to score the attractiveness of each smile separately using a visual analog scale. Results Smile attractiveness scores concerning the incisal edge positions of the maxillary central incisors were similar between the two groups. However, upper lip coverage was rated as unattractive by the younger group. A gingival display of 0 and 2 mm was rated as most attractive by the younger group. Upper lip coverage and gingival display of 0 and 2 mm were considered attractive by the older group. Excessive gingival display (6 mm) was scored as unattractive by both groups. A black triangle ranging from 1 to 2.5 mm between the maxillary central incisors was scored differently between the two groups. The older group was more tolerant of the black triangle size. Conclusions Age impacts smile perception based on maxillary gingival display and the presence of a black triangle between the maxillary central incisors, but not of the incisal edge position of the maxillary central incisors. Due to the variation in esthetic perception of each individual, participation between orthodontists and patients for decision-making and treatment planning is a crucial process to provide successful results.